(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The results of the 20-years investigation of the bryophytes with uncertain substrate ecology in the steppe zone of Ukraine are summarized. Based on the response to substrate chemistry, studied bryophytes are divided into 7 ecotype classes: calciphilous, acidophilous, calcifugous, siliciphilous, halophilous, nitrophilous and indifferent. The bryophytes with uncertain substrate ecology (we call them "incertophytes" from the Latin "incertus" - not clear, uncertain) are abundant in the steppe zone of Ukraine: 171 species = 54,6 % of the species composition. Incertophytes are absent from the substrates with clear tendences in chemistry (e.g. strongly calcareous or strongly acidic). Genera, which include lots of incertophytes, are: Sciurohypnum – 100,0%, Amblystegium - 80.0 %, Orthotrichum – 78,57 %, Bryum – 77,7 % and Brachythecium – 75,0%. All of the leading families of bryophytes in the steppe zone contain number of incertophytes: Orthotrichaceae – 78,5 %, Bryaceae and Brachytheciaceae - both 75.0 %, Ditrichaceae – 71,42 %, Amblystegiaceae - 647 %, Hypnaceae – 64,28 %, Funariaceae – 62,5 %.